Perioperative medicine - Cohn, Steven L. (Springer eBooks., 2011)
Contents undergoing surgery often have medical problems that may influence their perioperative risk. Optimal management involves collaboration of the health care team members including the medical consultant, anesthesiologist, and surgeon. Perioperative Medicine brings together the principles and practice of all phases of perioperative care ? preoperative, intraoperative, and postoperative. This book is a concise, yet comprehensive, review of perioperative medicine written and edited by leading experts in internal medicine, hospital medicine, and anesthesiology. It reviews the practical aspects of perioperative patient care, primarily from a medical view, and uses a bulleted format that condenses and highlights the key concepts for easy reference. It covers perioperative care from risk assessment to postoperative follow-up, including the role of the consultant, preoperative testing and risk assessment, perioperative medication management, and prophylactic measures, surgery-specific risks, and postoperative complications. The editor has over 25 years of experience in perioperative medical consultation at a large, academic medical center, and has used his expertise to focus on information useful to practicing clinicians. The target audience is generalists as well as specialists who are involved in perioperative patient care, including internists, hospitalists, anesthesiologists, surgeons, physicians' assistants, nurse anesthetists, and residents in training.